2016
DOI: 10.4238/gmr.15027631
|View full text |Cite
|
Sign up to set email alerts
|

Association between C677T and A1298C polymorphisms of the MTHFR gene and risk of male infertility: a meta-analysis

Abstract: ABSTRACT. Published studies on the association between the C677T and A1298C polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) gene and male infertility risk are controversial. To obtain a more precise evaluation, we performed a meta-analysis based on published case-control studies. We conducted an electronic search of PubMed, EMBASE, the Cochrane Library, the Web of Science, and the China Knowledge Resource Integrated Database for papers on MTHFR gene C677T and A1298C polymorphisms and male infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…There is accumulating evidence that there is a connection between thrombophilia factor MTHFR and infertility of both men and women (1,3,(10)(11)(12)(16)(17)(18). In females, the C677T mutation in the MTHFR gene greatly increases the risk of miscarriage (1,3,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that there is a connection between thrombophilia factor MTHFR and infertility of both men and women (1,3,(10)(11)(12)(16)(17)(18). In females, the C677T mutation in the MTHFR gene greatly increases the risk of miscarriage (1,3,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…While male infertility accounts for about half of infertility cases that characterize 15-20% of couples (9), to our knowledge there is no report of testing of the two major coagulation factor mutations in infertile men. Another common thrombophiliacausing mutation, C677T, in the methylene-tetrahydrofolate reductase (MTHFR) gene has been associated with both female and male infertility (10)(11)(12).…”
Section: Abstract Background: Thrombophilia-related Mutations Such mentioning
confidence: 99%
“…As a result, several meta-analyses addressing these associations have been performed. Three recent meta-analyses consistently showed that the MTHFR C677T polymorphism was associated with a significantly increased male infertility risk in the Asian and overall populations but not the Caucasian population[1113]. Two recent meta-analyses both showed that the MS A2756G polymorphism may be a genetic risk factor for idiopathic male infertility[13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent meta-analyses both showed that the MS A2756G polymorphism may be a genetic risk factor for idiopathic male infertility[13, 14]. Moreover, two recent meta-analyses were performed to examine the association between MTHFR A1298C and the risk of male infertility, the results were inconsistent[11, 13]. In the Chinese population, several studies have examined the associations between folate-related enzyme gene polymorphisms and the risk of male infertility; however, the results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation